1997
DOI: 10.1088/0954-3899/23/10/024
|View full text |Cite
|
Sign up to set email alerts
|

Near- and sub-barrier fission fragment anisotropies and the failure of the statistical theory of fission decay rates

Abstract: The angular distributions of fission fragments have been measured over a range of near-and sub-barrier energies for reactions involving 7 Li, 11 B, 12 C and 16 O projectiles on 232 Th, 235,236,238 U and 237 Np targets. The discrepancies between our experimental fission anisotropies and the transition state model increase dramatically as the beam energy decreases through the region of the fusion barriers; decrease smoothly with projectile size with a fixed target; show no evidence of a discontinuous behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 24 publications
1
43
1
Order By: Relevance
“…Similar observations were made by Refs. [25,26] using light projectiles ranging from 7 Li to 16 O on a range of actinide targets, confirming the effect of deformation on QF. However, measurements of ER cross sections for the 16 O + 238 U reaction showed that CN formation is still present at sub-barrier energies for this reaction [27].…”
Section: Introductionmentioning
confidence: 60%
“…Similar observations were made by Refs. [25,26] using light projectiles ranging from 7 Li to 16 O on a range of actinide targets, confirming the effect of deformation on QF. However, measurements of ER cross sections for the 16 O + 238 U reaction showed that CN formation is still present at sub-barrier energies for this reaction [27].…”
Section: Introductionmentioning
confidence: 60%
“…[19,54] is reasonable and allows the reproduction of the anisotropy of the angular distribution for heavy fissioning nuclei. The obtained relaxation time of the K coordinate τ K ∼ 10 −20 s is in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned value of the friction parameter γ K used in Refs. [17,19] was obtained by Lestone and coauthors in their early study [54] from an analysis of fission fragment angular distribution measured for a number of fusion-fission reactions. This value was further used in Refs.…”
Section: Modelmentioning
confidence: 99%
“…Experimental measurements of A have been selected from the literature [16,36,51,[62][63][64][65][66] for reactions of projectiles from B to S, bombarding targets of 232 Th and 238 U. Selection was based on consistency between measurements by different authors, the effectiveness of the method of separation of transfer- induced fission (and its likely influence on the anisotropies), and the consistent variation of A as a function of beam energy within a given experiment.…”
Section: Experimental Anisotropies For Reactions With Thu Targetsmentioning
confidence: 99%